PRICE BEHAVIOUR OF COPRA IN MAJOR MARKETS OF KERALA: A TIME SERIES ANALYSIS - Preethi V.P; Jesy Thomas K; Anil Kuruvila and Laly John C (IJRAR December, 2018)
Changes in the price behaviour of copra in major markets of Kerala ( Alappuzha and Kozhikode) were analysed for two periods viz., Period I (from 1980-01 to 1995-96) and Period II (from 1996-97 to 2015-16) and the variations in price due to trend, cyclical, seasonal and irregular fluctuations were calculated. For copra, these markets were observed to be more synchronised showing signs of better market integration during Period II. In spite of high fluctuations, the copra price moved in the two markets in close association with each other indicating mutual dependencies among these markets. It was observed that the seasonality and irregular variations in the price were more prominent in the primary commodity than the processed commodity like copra